2018
DOI: 10.1038/s41386-018-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of dorsal raphe serotonergic neurons modulates active coping to inescapable stress and anxiety-related behaviors in mice and rats

Abstract: Major depression and anxiety disorders are a social and economic burden worldwide. Serotonergic signaling has been implicated in the pathophysiology of these disorders and thus has been a crucial target for pharmacotherapy. However, the precise mechanisms underlying these disorders are still unclear. Here, we used species-optimized lentiviral vectors that were capable of efficient and specific transduction of serotonergic neurons in mice and rats for elucidation of serotonergic roles in anxiety-like behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 50 publications
3
61
0
Order By: Relevance
“…We and others previously reported that lentiviral vectors bearing the mouse and rat TPH2 promoter can selectively transduce 5-HT neurons in mice and rats, respectively [31,37]. To manipulate 5-HT neuronal activity not only at the cell soma region but also at the axon terminal region, we made an adeno-associated virus (AAV) bearing CheRiff, an optogenetic actuator that shows good expression and membrane trafficking [38], under the control of the mouse TPH2 promoter.…”
Section: Effect Of Optogenetic Activation Of Drn 5-ht Neurons Transdumentioning
confidence: 99%
See 2 more Smart Citations
“…We and others previously reported that lentiviral vectors bearing the mouse and rat TPH2 promoter can selectively transduce 5-HT neurons in mice and rats, respectively [31,37]. To manipulate 5-HT neuronal activity not only at the cell soma region but also at the axon terminal region, we made an adeno-associated virus (AAV) bearing CheRiff, an optogenetic actuator that shows good expression and membrane trafficking [38], under the control of the mouse TPH2 promoter.…”
Section: Effect Of Optogenetic Activation Of Drn 5-ht Neurons Transdumentioning
confidence: 99%
“…Previous reports have indicated the importance of 5-HT neuronal signaling in the pathophysiology and therapeutics of major depressive disorders [26][27][28][29]. Indeed, previous reports have demonstrated that the activation of DRN 5-HT neurons induces an antidepressant-like effect in mice and rats [30,31]. Similar to an antidepressive effect, rewarding potency of DRN 5-HT neurons has been studied by using several lines of genetically-modified mice [9][10][11][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these constructs, lentiviral and adeno-associated viral vectors were created for serotonin neuron targeting (Benzekhroufa et al, 2009). Moreover, these vectors were improved by optimizing the IRES site and adding the WPRE sequence to increase the expression level of the genes delivered by the retroviral vectors (Nishitani et al, 2019).…”
Section: Viral Vectorsmentioning
confidence: 99%
“…To deliver optogenetic proteins to serotonergic neurons of animals that had not been subjected to genetic modifications, lentiviral vectors based on the rat and mouse tph2 promoters were designed. They made it possible to study the differences in the depressive-like and anxious behavior of these species, stimulating the neurons of the dorsal raphe nucleus (Nishitani et al, 2019).…”
Section: Optogenetic and Chemogenetic Approachesmentioning
confidence: 99%